2019
DOI: 10.1097/shk.0000000000001221
|View full text |Cite
|
Sign up to set email alerts
|

Early Hyperoxia in The Intensive Care Unit is Significantly Associated With Unfavorable Neurological Outcomes in Patients With Mild-to-Moderate Aneurysmal Subarachnoid Hemorrhage

Abstract: Early hyperoxia was not associated with unfavorable neurological outcomes in overall SAH patients, but it was associated with unfavorable neurological outcomes in those with H&K grades I-III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
2
22
1
1
Order By: Relevance
“…On the other hand, a more recently published retrospective cohort study did not find a correlation between hyperoxia and the emergence of a poor neurological fallout (p=0.06). In contrast, in this study, the subgroup of patients with H&K I-III SAH exposed to hyperoxia had an unfavorable neurological prognosis (p=0.02) [10].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, a more recently published retrospective cohort study did not find a correlation between hyperoxia and the emergence of a poor neurological fallout (p=0.06). In contrast, in this study, the subgroup of patients with H&K I-III SAH exposed to hyperoxia had an unfavorable neurological prognosis (p=0.02) [10].…”
Section: Discussioncontrasting
confidence: 82%
“…Likewise, the study by Yokoyama et al found no association between a hyperoxic state and the development of ischemic events [10]. However, it is interesting to note that their PaO 2 threshold for defining hyperoxia was <120 mmHg.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…PaO 2 above 300 mm Hg was associated with increased mortality or poor neurological outcome in patients with post‐cardiac arrest resuscitated state or traumatic brain injury, while PaO 2 during cardiac arrest was independently associated with higher rates of survival to hospital discharge or neurological outcome in patients with cardiac arrest . Hyperoxia (PaO 2 > 300 mm Hg) during the first 24 hours in the ICU had no effect on neurological outcome in patients with subarachnoid haemorrhage . However, these data in the critically ill have focused on the outcome associated with relatively prolonged hyperoxia, with the assessment of hyperoxia exposure during the first 24‐72 hours of ICU stay through the entire period of MV.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, research has also focused on the role of hyperoxemia. In fact, PaO 2 levels > 100 mmHg seem to have deleterious effects on outcome in critically ill patients overall [6,7] and the threshold changes only slightly in specific subpopulations such as post-cardiac arrest (PaO 2 levels > 120 mmHg) [8,9] or aneurysmal subarachnoid hemorrhage (aSAH) (PaO 2 > 200 mmHg) patients [10]. Moreover, the concept of PaO 2 variability, defined as the daily difference between the highest and the lowest PaO 2 values, has recently been identified as a potential surrogate marker for relative ischemiareperfusion injury [11,12].…”
mentioning
confidence: 99%